Critical analysis of modified grouping efficacy measure; new weighted modified grouping efficiency measure. Issue 1 (1st January 2018) - Al-Bashir, Adnan; Mukattash, Adnan; Dahmani, Nadia; Al-Abed, Nizar
Abstract: Different grouping efficiency measures have been used to evaluate block-diagonal forms in group technology. One of the well-known measures is grouping efficacy. Many grouping efficiency measures were developed in the literature are based on or derived from grouping efficacy. One of these measures is called modified grouping efficacy (MGE). The limitation of MGE measure is that the case of zero efficiency can't be determined. Moreover, the efficiency of the system is close to zero or very low compared with other measures in the case, where the number of voids is greater than number of exceptions inside the cell. To overcome these limitations, a new measure called weighted modified grouping efficacy is developed in this paper. This measure is tested against some problems from the literature and the results demonstrate the ability of this measure to be used in the evaluation of all types of Structure data.